Antimicrobial and Probiotic Properties of Yeasts: From Fundamental to Novel Applications - Rima, Hatoum; Steve, Labrie; Ismail, Fliss (Frontiers in Microbiology, 2012)
The yeasts constitute a large and heterogeneous group of microorganisms that are currently attracting increased attention from scientists and industry. Numerous and diverse biological activities make them promising candidates for a wide range of applications not limited to the food sector. In addition to their major contribution to flavor development in fermented foods, their antagonistic activities toward undesirable bacteria, and fungi are now widely known. These activities are associated with their competitiveness for nutrients, acidification of their growth medium, their tolerance of high concentrations of ethanol, and release of antimicrobial compounds such as antifungal killer toxins or “mycocins” and antibacterial compounds. While the design of foods containing probiotics (microorganisms that confer health benefits) has focused primarily on Lactobacillus and Bifidobacterium, the yeast Saccharomyces cerevisiae var. boulardii has long been known effective for treating gastroenteritis. In this review, the antimicrobial activities of yeasts are examined. Mechanisms underlying this antagonistic activity as well as recent applications of these biologically active yeasts in both the medical and veterinary sectors are described.